FLOYD, RITA. SECURITY AND THE ENVIRONMENT: SECURITISATION THEORY AND US ENVIRONMENTAL SECURITY POLICY. CAMBRIDGE UNIVERSITY PRESS, 2010 - Tesche, Ana Bárbara Moreira (Revista Brasileira de Estudos de Defesa, 2014)
ISBN: 9780521197564